2011
DOI: 10.1007/s13355-011-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the winter cherry bug Acanthocoris sordidus (Hemiptera: Coreidae) and its egg parasitic wasps

Abstract: Detailed research on the relative strength of the influence of parasitoids on hosts has contributed to the development of biological control techniques. Gryon philippinense (Ashmead) is a major egg parasitoid of the winter cherry bug, Acanthocoris sordidus (Thunberg). However, available data are insufficient to determine which egg parasitoids have the strongest effect on mortality of A. sordidus or why G. philippinense is the major egg parasitoid of A. sordidus. In this study, G. philippinense attained a much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…O sucesso de programas de controle biológico de insetospragas depende da disponibilidade de técnicas de criação em larga escala de parasitoides e seus hospedeiros, bem como do conhecimento de suas interações biológicas (PEREIRA et al, 2010 a, b;PASTORI et al, 2010;NAKAJIMA;NAKAGAWA;FUJISAKI, 2012). Diatraea saccharalis pode ser criada em grandes quantidades e sua pupa é adequada para o desenvolvimento de T. howardi, o que demonstra o potencial desse hospedeiro para ser utilizado em criações massivas do parasitoide (CRUZ et al, 2011).…”
Section: Introductionunclassified
“…O sucesso de programas de controle biológico de insetospragas depende da disponibilidade de técnicas de criação em larga escala de parasitoides e seus hospedeiros, bem como do conhecimento de suas interações biológicas (PEREIRA et al, 2010 a, b;PASTORI et al, 2010;NAKAJIMA;NAKAGAWA;FUJISAKI, 2012). Diatraea saccharalis pode ser criada em grandes quantidades e sua pupa é adequada para o desenvolvimento de T. howardi, o que demonstra o potencial desse hospedeiro para ser utilizado em criações massivas do parasitoide (CRUZ et al, 2011).…”
Section: Introductionunclassified
“…Females of A. sordidus lay eggs both on and off their host plants Nakajima et al 2011). When they oviposit off their host plants, the second-instar nymphs must search for their host plants to survive, because the second instar is the first feeding stage.…”
Section: Discussionmentioning
confidence: 99%
“…Nakajima et al (2011) found that egg clusters of A. sordidus were laid with roughly equal frequency on both host and non-host plants in Kyoto (35°00 0 N, 135°46 0 E) and Kochi prefectures (33°33 0 N, 133°40 0 E) in Japan; most of them were laid away from host plants on Amami Island, Kagoshima Prefecture, Japan (28°24 0 N, 129°35 0 E). We revealed that oviposition on nonhost plants by A. sordidus decreased egg mortality by providing their eggs with a refuge from ground-living arthropod predators, but increased nymphal mortality by imposing host-searching costs on their nymphs .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The winter cherry bug, Acanthocoris sordidus Thunberg (Hemiptera: Coreidae), is widely spread in Korea, Japan, and Taiwan (Nakajima et al 2011), feeding on the plant species of Convolvulaceae and Solanaceae (Fujisaki 1980(Fujisaki , 1981. It may pose a serious threat to vegetable crops in greenhouses where the use of pollinators and natural enemies requires minimal use of chemical pesticides (Dasilao & Arakawa 2004).…”
Section: Introductionmentioning
confidence: 99%